2016
DOI: 10.1021/acs.macromol.6b01374
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Morphological Transitions of Photoreactive and Thermoresponsive Vesicles for Controlled Release and Nanoreactors

Abstract: The construction of intelligent vesicular nanocarriers and nanoreactors has received increasing interests due to their potential in mimicking natural counterparts such as cells and organelles. Herein, we report thermoresponsive and photoreactive vesicles could be fabricated from amphiphilic block copolymers (BCPs), poly(N-isopropylacrylamide)-b-poly(2-((((2-nitrobenzyl)oxy)carbonyl)amino)ethyl acrylate) (PNIPAM-b-PNBOCA), which were synthesized via consecutive reversible addition−fragmentation chain transfer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…1). 2-Nitrobenzyl ester photo-caged carboxyl monomer (NCMA) and disulfide-caged carboxyl monomer (DCMA) generate carboxyl moieties upon actuation of UV irradiation and reductive milieu, respectively [26][27][28] . For the second series, pH-responsive DPA and DEA monomers containing both carbamate linkage and tertiary amine moieties were synthesized ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 2-Nitrobenzyl ester photo-caged carboxyl monomer (NCMA) and disulfide-caged carboxyl monomer (DCMA) generate carboxyl moieties upon actuation of UV irradiation and reductive milieu, respectively [26][27][28] . For the second series, pH-responsive DPA and DEA monomers containing both carbamate linkage and tertiary amine moieties were synthesized ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). We intentionally integrate carbamate linkage into both tertiary amine-containing comonomers and caged carboxyl comonomers to strengthen intra-and inter-chain HB interactions within vesicle bilayers [26][27][28]52 , which provide a pre-organized milieu for cooperative noncovalent interactions with directional orientation and high local concentration. Upon triggered cleavage and generation of carboxyl moieties within bilayers, proton transfer from carboxyl to tertiary amine in situ generates ionized carboxyl and protonated amine moieties.…”
Section: A-(bc)mentioning
confidence: 99%
See 1 more Smart Citation
“…On a different approach, polymersomes with switchable permeability under UV light have also been employed as enzymatic nanoreactors . Yao et al encapsulated the GOx enzyme within polymersomes consisting of poly( N ‐isopropylacrylamide)‐ b ‐poly(2((((2‐nitrobenzyl)oxy)‐carbonyl)amino)ethyl acrylate) (PNIPAM‐ b ‐PNBOCA).…”
Section: Micro/nanosized Single‐compartment Enzymatic Reactorsmentioning
confidence: 99%
“…Investigations have shown that the morphology of the carriers plays an essential role in influencing their release behavior. Therefore, drug carriers prepared from stimuli-responsive polymers that can be (self-)assembled in varying morphologies have been explored, such as vesicles, 15,17 micelles, [18][19][20] nanogels, [21][22][23] nanofibers, 6,[24][25][26] and so forth, each with certain advantages and disadvantages. Among them, "smart" nanofibers as drug carriers have attracted great interest due to their unique features.…”
mentioning
confidence: 99%